2007
DOI: 10.1088/0953-4075/40/7/006
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Stark effect in υ+= 0 Rydberg states of NO with a matrix-diagonalization analysis

Abstract: Rydberg states with the principal quantum number n = 25-32, below the υ + = 0 ionization limit, are excited by double resonance via the υ = 0, N = 0 and υ = 0, N = 2 rovibrational states of the A 2 + state. In the presence of dc electric fields in the range 0-120 V cm −1 , new resonances and hydrogenic manifolds are observed. The experimental spectra are simulated using a matrixdiagonalization approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…In the range under study, it appears that all the optically populated states are predissociated on this timescale. The work reported here is complementary to recent studies of Fielding and co-workers [16] in which the states that are long lived with respect to predissociation, principally the nf series and other levels mixed with those series by the field, are detected by pulsed field ionisation. It also covers the lower-n region, 13-16, where the electronic spacing is larger than the rotational spacing, as distinct from the n ¼ 25-32 region in [16] where the switch in relative sizes of these quanta occurs.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the range under study, it appears that all the optically populated states are predissociated on this timescale. The work reported here is complementary to recent studies of Fielding and co-workers [16] in which the states that are long lived with respect to predissociation, principally the nf series and other levels mixed with those series by the field, are detected by pulsed field ionisation. It also covers the lower-n region, 13-16, where the electronic spacing is larger than the rotational spacing, as distinct from the n ¼ 25-32 region in [16] where the switch in relative sizes of these quanta occurs.…”
Section: Introductionsupporting
confidence: 79%
“…Molecular Rydberg states are highly susceptible to the effects of external fields, and these effects are of importance in a number of new applications of Rydberg states [1], including the deceleration and deflection of Rydberg molecule beams [2][3][4][5][6], and recent experiments involving the scattering of Rydberg molecules at surfaces [7,8]. Previous spectroscopic studies of the Stark effect in molecular Rydberg states, primarily in H 2 [8][9][10], Li 2 [11] H 3 [12] and NO [13][14][15][16], have focused on either autoionising states which lie above the ionisation threshold, or those states that are sufficiently long lived and near to threshold to be detected by field ionisation. The requirement for long-lived character implies that the only states observed are those which are relatively immune to predissociation [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To satisfy parity criteria and propensity rules [30,33,34], we expect strong transitions from the s component to np Rydberg series with N + = N , from the d component to np and nf series with N + = N , N ± 2, and weaker transitions from the p component to ns and nd series with N + = N ± 1. Vibrational transitions are controlled by the fact that the overriding Franck-Condon factor is for υ = 0 transitions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Softley and co-workers studied the effect of external electric fields on low Rydberg states of NO with principal quantum number n < 20 [29,30], and Vrakking and Lee investigated the Stark effect in much higher Rydberg states, where n = 40-120 [31]. In our own group, we have studied the intermediate Rydberg states of NO, with principal quantum number n = 25-35 in static and ramped external fields [32][33][34]. We have also investigated the dynamics of Rydberg electron wave packets in NO [35][36][37] and demonstrated that it is possible to control the composition of the wave packet by employing phase-locked pairs of optical pulses [1,2].…”
Section: Introductionmentioning
confidence: 99%